KEBIJAKAN UIN SUNAN KALIJAGA DALAM PENGUATAN BUDAYA MENULIS MAHASISWA DI MEDIA MASSA - Faisal Ismail (Hikmah, 2019)
Focusing on the journalism indeed is not always associated with certain mass media. One can be a freelance journalist and still having some free time. This is made possible by being a freelance writer writing columns. Columns on the mass media are open for public. This means a good opportunity for university students, who are used to critical thinking. University students in their role as a social control related to various problems in the society do not have to go to the streets but they can do so by the mass media writing activities.Building a mass media writing culture in the students requires a real support from Universities. With the existing policy, students are expected to actively write on the mass media columns. Looking at the number of the mass media columns, students by all means have many choices. There are several columns on the mass media, ranging from columns on news, opinions, features, short stories, poems, book reviews, etc. Newspapers are mostly about news, and the news writers are the permanent journalists in that newspapers office. Permanent journalists have a contract and fixed income from the media where they work, while articles, book reviews, and features are columns open for public. They who actively write articles are also called freelance journalists. As freelance journalists, they do not have contracts with certain media, and the income they get corresponds to the number of published articles.Keyword: journalism, mass media, columns, university students, journalists Menekuni bidang jurnalistik sesungguhnya tidak harus selalu terikat dengan media massa tertentu. Seseorang bisa menjadi wartawan lepas dengan waktu yang tidak terlalu terikat. Hal itu bisa dilakukan dengan menjadi penulis lepas (freelance) lewat rubrik (kolom)  artikel. Kolom artikel di media massa terbuka untuk umum. Ini berarti merupakan kesempatan yang baik untuk mahasiswa yang terbiasa berpikir kritis. Mahasiswa dalam melakukan kontrol sosial terkait dengan berbagai problem sosial di tengah masyarakat, tidak harus turun ke jalan, melainkan bisa dilakukan dengan aktivitas menulis di media massa.Membangun budaya menulis bagi mahasiswa di media massa tentu perlu ada dukungan nyata Perguruan Tinggi. Dengan kebijkan yang ada diharapkan mahasiswa bisa aktif mengisi berbagai rubrik yang ada di media massa. Dilihat dari rubrik yang ada di media massa, tentu banyak pilihan bagi mahasiswa. Ada beberap rubrik yang di media massa, mulai dari rubrik berita, artikel (opini), feature,  cerpen, puisi, resensi buku dll. Sebagian besar isi surat kabar adalah berita, dan penulis berita adalah wartawan tetap di surat kabar tersebut. Wartawan tetap berarti mempunyai ikatan dan penghasilan tetap dari media tempatnya bekerja. Sedangkan artikel, resensi buku, dan feature adalah kolom  yang terbuka untuk umum. Mereka yang aktif dalam menulis artikel disebut juga dengan wartawan freelance (penulis lepas). Sebagai penulis lepas, mereka tidak terikat dengan media tertentu, dan penghasilan (honor)  yang mereka peroleh sesuai dengan jumlah tulisan yang dimuat.Kata Kunci: jurnalistik, media massa, rubrik, mahasiswa, wartawan